Resistance‐associated substitutions in patients with chronic hepatitis C virus genotype 4 infection. Issue 10 (26th June 2020) - Dietz, Julia; Kalinina, Olga V.; Vermehren, Johannes; Peiffer, Kai‐Henrik; Matschenz, Katrin; Buggisch, Peter; Niederau, Claus; Schattenberg, Jörn M.; Müllhaupt, Beat; Yerly, Sabine; Ringelhan, Marc; Schmid, Roland M.; et al.
Abstract: Data on the prevalence of resistance‐associated substitutions (RASs) and their implications for treatment with direct‐acting antivirals (DAAs) are sparse in European patients with HCV genotype 4. This study investigated RASs before and after DAA failure in different genotype 4 subtypes and evaluated retreatment efficacies. Samples of 195 genotype 4‐infected patients were collected in the European Resistance Database and investigated for NS3, NS5A and NS5B RASs. Retreatment efficacies in DAA failure patients were analysed retrospectively. After NS5A inhibitor (NS5Ai) failure, subtype 4r was frequent (30%) compared to DAA‐naïve patients (5%) and the number of NS5A RASs was significantly higher in subtype 4r compared to 4a or 4d (median three RASs vs no or one RAS, respectively, P < .0001). RASsL28V, L30R and M31L pre‐existed in subtype 4r and were maintained after NS5Ai failure. Typical subtype 4r RASs were located in subdomain 1a of NS5A, close to membrane interaction and protein‐protein interaction sites that are responsible for multimerization and hence viral replication. Retreatment of 37 DAA failure patients was highly effective with 100% SVR in prior SOF/RBV, PI/SOF and PI/NS5Ai failures. Secondary virologic failures were rare (n = 2; subtype 4d and 4r) and only observed in prior NS5Ai/SOF failures (SVR 90%). In conclusion, subtype 4r harboured considerably more RASs compared to other subtypes. A resistance‐tailored retreatment using first‐ and second‐generation DAAs was highly effective with SVR rates ≥90% across all subtypes and first‐line treatment regimens.